Association of cold weather with testicular torsion. Issue 6353 (20th November 1982) - Shukla, R B; Kelly, D G; Daly, L; Guiney, E J
Abstract : A retrospective study of 46 patients who presented with proved testicular torsion over five years at two Dublin hospitals showed that in 40 cases torsion had occurred when the temperature was under 2 degrees C; the incidence of torsion was higher during the cold months of the year. Both of these findings were statistically significant. These and other results suggest that the ambient temperature may have some role in the incidence and aetiology of testicular torsion.